1999
DOI: 10.1165/ajrcmb.20.4.3439
|View full text |Cite
|
Sign up to set email alerts
|

Glycoprotein-340 Binds Surfactant Protein-A (SP-A) and Stimulates Alveolar Macrophage Migration in an SP-A–Independent Manner

Abstract: Glycoprotein-340 (gp-340) was first identified as a surfactant protein (SP)-D-binding molecule purified from lung lavage of patients with alveolar proteinosis (Holmskov, et al., J. Biol. Chem. 1997;272:13743). In purifying SP-A from proteinosis lavage, we isolated a protein that copurifies with SP-A and SP-D and that was later found by protein sequencing to be gp-340. We have shown that soluble gp-340 binds SP-A in a calcium-dependent manner independent of the lectin activity of SP-A. To examine the functional… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

1
107
0

Year Published

1999
1999
2014
2014

Publication Types

Select...
9

Relationship

1
8

Authors

Journals

citations
Cited by 97 publications
(108 citation statements)
references
References 41 publications
1
107
0
Order By: Relevance
“…SRCR proteins, e.g. the macrophage scavenger receptor, Mac-2-binding protein, CD5, CD6, WC1, Ebnerin, CRP (cyclic AMP receptor protein)-ductin, and lung gp-340, are associated with host defense systems (7,8,(11)(12)(13)(14)(15)(16)(17). Until now, studies dealing with agglutinin-bacteria interactions have been focused mainly on the characterization of bacterial receptors (18,19) and identification of their cognate carbohydrate ligands on agglutinin (1, 20 -22).…”
mentioning
confidence: 99%
“…SRCR proteins, e.g. the macrophage scavenger receptor, Mac-2-binding protein, CD5, CD6, WC1, Ebnerin, CRP (cyclic AMP receptor protein)-ductin, and lung gp-340, are associated with host defense systems (7,8,(11)(12)(13)(14)(15)(16)(17). Until now, studies dealing with agglutinin-bacteria interactions have been focused mainly on the characterization of bacterial receptors (18,19) and identification of their cognate carbohydrate ligands on agglutinin (1, 20 -22).…”
mentioning
confidence: 99%
“…It has also been established that the binding of SP-D to gp-340 is a protein-protein interaction rather than a lectin-carbohydrate interaction. Recently, it was shown that gp-340 also may bind to SP-A (17). Protein sequencing showed that gp-340 was a member of the scavenger receptor cysteine-rich (SRCR) superfamily (16).…”
mentioning
confidence: 99%
“…Recently, gp-340 also has been shown to bind SP-A in a calcium-dependent manner that is independent of the latter's lectin activity (17), but gp-340 neither affected the binding of SP-A to alveolar macrophages nor inhibited the ability of SP-A to stimulate macrophage chemotaxis. It was shown that gp-340 alone stimulates the random migration of alveolar macrophages in a manner independent of SP-A-stimulated chemotaxis.…”
mentioning
confidence: 99%
“…Additionally, the scavenger protein glycoprotein-340 binds SPA in a carbohydrate recognition domain-independent manner, but it does not affect binding of SPA to alveolar macrophages or SPA stimulation of macrophage chemotaxis. However, glycoprotein-340 directly stimulates random migration (chemokinesis) of alveolar macrophages (48). SPA can also bind to CD14, a known pattern recognition co-receptor for LPS and PGN, that mediates release of pro-inflammatory cytokines (49).…”
Section: Discussionmentioning
confidence: 99%